2023
DOI: 10.1038/s41612-023-00354-x
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Oscillation impact on the Atlantic Meridional Overturning Circulation shaped by the mean state

Abstract: Accurate representation of the Atlantic Meridional Overturning Circulation (AMOC) in global climate models is crucial for reliable future climate predictions and projections. In this study, we used 42 coupled atmosphere–ocean global climate models to analyze low-frequency variability of the AMOC driven by the North Atlantic Oscillation (NAO). Our results showed that the influence of the simulated NAO on the AMOC differs significantly between the models. We showed that the large intermodel diversity originates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Note that the wave train is consistently shown in the boreal winter (DJF), when both the Rossby wave teleconnection and the SPNA deep convection are dominant (Figure S5 in Supporting Information ). The NAO is known to modulate the AMOC intensity through the surface buoyancy response in the deep convection regions, a relationship corroborated by many climate models, including the employed model (e.g., Delworth & Zeng, 2016; Kim et al., 2023; Medhaug et al., 2012). In alignment with this, the presence of an anticyclone over Greenland corresponds to a weakening of the surface westerly winds over the SPNA, resulting in a significant reduction of regional evaporation (Figure 3b).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Note that the wave train is consistently shown in the boreal winter (DJF), when both the Rossby wave teleconnection and the SPNA deep convection are dominant (Figure S5 in Supporting Information ). The NAO is known to modulate the AMOC intensity through the surface buoyancy response in the deep convection regions, a relationship corroborated by many climate models, including the employed model (e.g., Delworth & Zeng, 2016; Kim et al., 2023; Medhaug et al., 2012). In alignment with this, the presence of an anticyclone over Greenland corresponds to a weakening of the surface westerly winds over the SPNA, resulting in a significant reduction of regional evaporation (Figure 3b).…”
Section: Resultsmentioning
confidence: 65%
“…For example, the AMOC is known as notorious spread among current climate models (e.g., Gong et al., 2022). Thus, even if the atmospheric teleconnection rapidly adjusts the AMOC, the magnitude of the adjustment would be highly variable across models (e.g., Kim et al., 2023). In addition, although the tropical response is similar to that shown in the studies imposing the Antarctic meltwater (Bronselaer et al., 2018; Oh et al., 2020), some models project a similar weakened convection in response to the Antarctic sea‐ice loss, which accompanies with surface warming (e.g., Ayres et al., 2022; England, Polvani, et al., 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This confirms the driving role of NAO in AMOC interdecadal variability. Actually, numerous model simulations have demonstrated that NAO variability exerts a significant impact on AMOC variability across interannual to interdecadal timescales (Jackson et al, 2022;Kim et al, 2023;Olsen et al, 2012;X. Wang et al, 2017).…”
Section: Atmospheric Processesmentioning
confidence: 99%
“…This confirms the driving role of NAO in AMOC interdecadal variability. Actually, numerous model simulations have demonstrated that NAO variability exerts a significant impact on AMOC variability across interannual to interdecadal timescales (Jackson et al., 2022; Kim et al., 2023; Olsen et al., 2012; X. Wang et al., 2017). This influence is primarily realized through the NAO's effect on the surface wind field and air‐sea buoyancy fluxes (Buckley & Marshall, 2016; Delworth & Zeng, 2016; Visbeck et al., 1998; Zhang et al., 2019).…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation